Strategies for Managing Educational Collaboration Networks in Schools under the Bueng Kan Primary Educational Service Area Office - Ngonmanee, Eknarin; Phakamach, Phongsak; Maneewong, Somjai (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to: 1) study the components of managing educational collaboration networks of schools under the Bueng Kan Primary Educational Service Area Office, 2) examine the current and desirable conditions of network management, 3) develop strategies for managing educational collaboration networks, and 4) evaluate the suitability, feasibility, and utility of the developed strategies. The study employed a mixed-methods approach conducted in three phases: studying components and needs, developing strategies through expert group meetings, and verifying the suitability, feasibility, and utility of the strategies. The sample consisted of 340 school administrators and teachers selected through multi-stage random sampling. Research instruments included questionnaires, interviews, and expert group discussions. Quantitative data were analyzed using descriptive statistics and the Modified Priority Needs Index (PNIModified), while qualitative data were analyzed through content analysis. The findings revealed that the components of managing educational collaboration networks comprised eight aspects: 1) collaborative planning, 2) implementation of plans, 3) coordination among network partners, 4) capacity building of the network, 5) interaction and communication, 6) participation of the network, 7) supervision and monitoring of collaboration, and 8) evaluation and improvement. The developed strategies consisted of six key elements: vision, mission, goals, strategic practices, projects/activities, and indicators. Expert evaluation confirmed that the strategies were rated at the highest level in terms of suitability, feasibility, and utility. Therefore, schools should adopt these strategies as guidelines for improving educational quality. Educational service areas should provide resources and coordination, while the Ministry of Education should establish policies to promote educational collaboration networks, thereby enhancing the quality of primary schools.